2021
DOI: 10.3390/foods10051124
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary and Pharmaceutical Approach to Natural Antimicrobials against Clostridioides difficile Gastrointestinal Infection

Abstract: Incidence of Clostridioides difficile infection (CDI) has been increasing in recent decades due to different factors, namely (i) extended use of broad-spectrum antibiotics, (ii) transmission within asymptomatic and susceptible patients, and (iii) unbalanced gastrointestinal microbiome and collateral diseases that favor C. difficile gastrointestinal domination and toxin production. Although antibiotic therapies have resulted in successful control of CDI in the last 20 years, the development of novel strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
(150 reference statements)
1
2
0
Order By: Relevance
“…Also, an in vitro study [55] observed the synergistic effect of the sub-MIC (1/2 MIC) berberine chloride with vancomycin. Bearing in mind the data presented, we can agree with the statement [62], that natural antimicrobial agents derived from plant sources are an innovative and sustainable option in controlling pathogens. However, it is necessary to investigate in vivo efficiency and toxicological safety of herbal products, as well as their effects on normal intestinal microbiota.…”
Section: Rootsupporting
confidence: 71%
“…Also, an in vitro study [55] observed the synergistic effect of the sub-MIC (1/2 MIC) berberine chloride with vancomycin. Bearing in mind the data presented, we can agree with the statement [62], that natural antimicrobial agents derived from plant sources are an innovative and sustainable option in controlling pathogens. However, it is necessary to investigate in vivo efficiency and toxicological safety of herbal products, as well as their effects on normal intestinal microbiota.…”
Section: Rootsupporting
confidence: 71%
“…Natural antimicrobial agents derived from plant sources are an innovative and sustainable option in controlling pathogens (Tortajada‐Girbes et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The rapid emergence of hypervirulent C. difficile isolates (Mody et al 2020) and the resistance of C. difficile to conventional antibiotic therapy encourage the development of new strategies for its control. Natural antimicrobial agents derived from plant sources are an innovative and sustainable option in controlling pathogens (Tortajada-Girbes et al 2021).…”
Section: Resultsmentioning
confidence: 99%